2010
DOI: 10.1029/2010jc006423
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of zonal current variations associated with the Indian Ocean dipole

Abstract: [1] This study examines interannual variability in the equatorial Indian Ocean using observations and a continuously stratified linear long-wave ocean model driven by European Centre for Medium-Range Weather Forecasts winds. Our focus is on the relationship between wind stress, zonal velocity, and sea surface height (SSH) in association with the Indian Ocean dipole (IOD). The model correctly simulates the dominant pattern of variability associated with the IOD in which SSH anomalies near the equator tend to ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 46 publications
13
68
0
1
Order By: Relevance
“…The first EOF mode (EOF1) of zonal currents and wind stress (Figure 4a) shows easterly wind stress peaking at about 85 E, while the zonal current peaks further west at about 75 E. Peak correlation between zonal currents and winds is 0.8, with zonal currents leading zonal winds by about a month (Figure 5a). This phase relationship is unexpected if we think only in terms of direct wind-forcing of the ocean and it is most likely due to influence on zonal current variability of reflected Rossby waves generated at the eastern boundary [Nagura and McPhaden, 2010b]. EOF1 accounts for 80% (67%) of the zonal current (windstress) variance.…”
Section: Interannual Variability Of the Wyrtki Jetsmentioning
confidence: 94%
See 1 more Smart Citation
“…The first EOF mode (EOF1) of zonal currents and wind stress (Figure 4a) shows easterly wind stress peaking at about 85 E, while the zonal current peaks further west at about 75 E. Peak correlation between zonal currents and winds is 0.8, with zonal currents leading zonal winds by about a month (Figure 5a). This phase relationship is unexpected if we think only in terms of direct wind-forcing of the ocean and it is most likely due to influence on zonal current variability of reflected Rossby waves generated at the eastern boundary [Nagura and McPhaden, 2010b]. EOF1 accounts for 80% (67%) of the zonal current (windstress) variance.…”
Section: Interannual Variability Of the Wyrtki Jetsmentioning
confidence: 94%
“…Thompson et al [2006], using the modular ocean model (MOM4), carried out extensive analysis on the anomalous zonal and meridional circulation associated with IOD. The anomalous winds associated with IOD are maximum over the central equatorial Indian Ocean and act as a direct local forcing, though westward propagating Rossby waves generated at the eastern boundary are also important [Nagura and McPhaden, 2010b].…”
Section: Introductionmentioning
confidence: 99%
“…The dipole pattern may affect the entire tropical Indian Ocean and is strongly expressed on a zonal dome or ridge in the thermocline which occurs on 4º-12º S between 45º-90º E. In-situ observations have been used to link the processes involved (Jury and Harrison, 1999;Roemmich and Owens, 2000;Ehrlich et al, 2002); and data from an array of moored buoys covering the tropical Indian Ocean is now available (McPhaden et al, 2009). Interannual oscillations of SST in the southern tropics are governed by wind-forced Rossby waves that undulate westward on the well known thermocline ridge (McCreary et al, 1993;Sengupta et al, 2001;Xie et al, 2001;Huang and Kinter, 2002;Jury and Huang, 2004;Nagura and McPhaden, 2010). Coupled models have been evaluated to determine their ability to represent this feature and its impacts (Behera et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In April strong westerly wind anomalies occurred along the equator that forced eastward zonal current anomalies, which are associated with the down welling equatorial Kelvin waves. Note that the eastward zonal current anomalies reveal westward phase propagation during April -May indicating the important role of Rossby waves in generating this westward phase propagation (Nagura and McPhaden 2010b). Previous studies have shown that the eastern-boundary reflected upwelling Rossby waves from the incoming upwelling Kelvin waves play an important role in zonal current variations along the equatorial Indian Ocean McPhaden 2010b: Iskandar et al 2013).…”
Section: Role Of Equatorial Wavesmentioning
confidence: 79%